Inertial migration of oblate spheroids in a plane channel - Nizkaya, Tatiana V.; Gekova, Anna S.; Harting, Jens; Asmolov, Evgeny S.; Vinogradova, Olga I. (Physics of Fluids, 2020)
We discuss an inertial migration of oblate spheroids in a plane channel, where the steady laminar flow is generated by a pressure gradient. Our lattice Boltzmann simulations show that spheroids orient in the flow, so that their minor axis coincides with the vorticity direction (a log-rolling motion). Interestingly, for spheroids of moderate aspect ratios, the equilibrium positions relative to the channel walls depend only on their equatorial radius a. By analyzing the inertial lift force, we argue that this force is proportional to a3b, where b is the polar radius, and conclude that the dimensionless lift coefficient of the oblate spheroid does not depend on b and is equal to that of the sphere of radius a.
CRIS-Team Scopus Importer:2020-12-11